Hydrothermal synthesized Nd-doped TiO2 with Anatase and Brookite phases as highly improved photoanode for dye-sensitized solar cell. (15th September 2020) - Neetu; Singh, Shalini; Srivastava, Pankaj; Bahadur, Lal
Graphical abstract: Highlights: Nd-TiO2 having Anatase and Brookite phases at high temperature by hydrothermal method. Higher efficiency DSSC with TiO2 Anatase and Brookite structure mixed photoanode. Nd-TiO2 photoanode based cell exhibiting significantly enhanced cell efficiency. Nd-TiO2 exhibiting increased dye loading and facile charge transfer characteristics. Abstract: In this study, the effects of Nd doping on the performance of TiO2 photoanode based dye-sensitized solar cells (DSSC) are reported. Nd-doped TiO2 (Nd-TiO2 ) was synthesized using hydrothermal method. Un-doped TiO2 (TiO2 ) was also synthesized for reference. XRD, IR, Raman and electron microscopy characterisation of the obtained material were performed and the subsequent electrochemical tests, CV and EIS studies were made to explore their application. The XRD and Raman analysis's results indicated that the Nd-TiO2 and TiO2 have both the Anatase and Brookite phases. TEM, EDX and EIS studies were used to obtain particle size, morphology, the presence of the element, electron lifetime and recombination characteristics respectively. The Nd-TiO2 nanoparticles have uniform particle size, a strong red shift of their absorption into the visible region and greater dye-loading as compared with TiO2 nanoparticles. It is proved that higher efficiency was achieved when the TiO2 Anatase and Brookite structure were mixed. Further, Nd had a positive effect on the performance of photoelectrode and DSSC fabricated with Nd-TiO2 photoanode revealed an appreciable current conversion efficiency of 5.23% with a short-circuit current ( J sc ) of 12.8 mA/cm 2, open-circuit voltage ( V oc ) of 0.62 V and fill factor ( FF ) of 0.66. The increased current conversion efficiency was attributed to the greater dye loading, reduced charge recombination and facile charge transport with Nd-doped TiO2 .